Efficacy of an electrically active sonic toothbrush and an oscillating/rotating powered toothbrush in the reduction of plaque and gingivitis: A comparative clinical trial - Himanshu Dadlani; M G Triveni; D S Mehta (Wolters Kluwer Medknow Publications, 2010)
Objectives: The purpose of the present study was to clinically evaluate and compare the efficacy of an electrically active sonic toothbrush and an oscillating/rotating powered toothbrush in the reduction of plaque and gingivitis. Material and Methods: For this study, 40 healthy student volunteers (20 males, 20 females) were selected. The subjects were randomly assigned into two groups by a second examiner; one group used a current producing sonic toothbrush and the other group used a battery powered toothbrush. Plaque Index, Modified Gingival Index and Gingival Bleeding Index were assessed at baseline, 15 th day, 30 th day, 45 th day and 60 th day. Results: All the baseline indices appeared to be well balanced. At the end of the study, reduction in plaque index, modified gingival index and gingival bleeding index were statistically highly significant during each interval for both the toothbrushes. The difference in reduction of clinical parameters between the two toothbrushes was statistically non significant. Conclusion: Both the toothbrushes used in this study were clinically effective in removing plaque and improving gingival health.